Pharmacokinetic study of Strongylocentrotus nudus egg polysaccharide in rats and beagles using a 3H-labeling method - Xing, Han; Zhu, Xiaojie; Liao, Jianmin; Kong, Ying; Lu, Yayuan; Zhao, Di; Li, Ning; Chen, Xijing; Qin, Zhiying (Frontiers in Pharmacology, 2023)
Strongylocentrotus nudus egg polysaccharide (SEP) extracted from sea urchins has the potential anticancer activity. However, little is known about its pharmacokinetic properties. To investigate the pharmacokinetics of SEP it was radio labeled by tritium. Furthermore, a sensitive, selective and rapid liquid scintillation counter (LSC) method for quantification of 3H-SEP in biological matrix was validated. The lower limit of quantification of the method was 4 Bq. The relative standard deviations (RSD) of the intra- and inter-day precision was <3.0% and <3.9% respectively. It was successfully applied to investigate the pharmacokinetics of SEP after intravenous administration of 20, 40, 80 mg/kg (40 μCi/kg) in rats and 5, 10, 20 mg/kg (6 μCi/kg) in beagles. The AUC（0-t）of SEP at three different doses was 487.81 ± 39.99 mg/L*h, 1003.10 ± 95.94 mg/L*h, 2188.84 ± 137.73 mg/L*h in rats and 144.12 ± 3.78 mg/L*h, 322.62 ± 28.03 mg/L*h, 754.17 ± 37.79 mg/L*h in beagle dogs, respectively. The terminal elimination half life (t1/2) of SEP was longer in beagles (204.29±139.34 h) than in rats (35.48±6.04 h). Concentration of SEP in plasma declined rapidly both in rats and beagles. All of the study results provided detailed pharmacokinetic profile of SEP in two kinds of animals, which was helpful for further development.